Уха из золотой рыбки: роман / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2003)
Экземпляры: 23 (20150414) / Инвентарный номер: 59091 / Цена: 110.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6